Women, politics, and power a global perspective - Paxton, Pamela Marie (Thousand Oaks SAGE Publications, 2014)
Women, Politics, and Power provides a clear and detailed introduction to women?s political participation and representation across a wide range of countries and regions. Using broad statistical overviews and detailed case-study accounts, authors Pamela Paxton and Melanie Hughes document both historical trends and the contemporary state of women?s political strength across diverse countries. In addition to describing worldwide themes, the book acknowledges differences among women through attention to intersectionality and heterogeneity among women. Dedicated chapters on six geographic regions highlight the distinct paths women may take to political power in different parts of the world. There is simply no other book that offers such a thorough and multidisciplinary synthesis of research on women?s political power around the world.
Includes bibliographical references and index.
Keywords: Women --Political activity